Cefiderocol - a promising new antibiotic for the antibiotic-resistant pathogens of the highest epidemiological priority - Lorenc, Karol Lorenc; Kozioł, Magdalena; Sobek, Alicja; Pawlicki, Mateusz; Łopuszyńska, Anna; Misztal, Zofia; Lewicki, Marcin; Smoleń, Agata (Journal of Education, Health and Sport, 2019)
Increase in the incidence of multidrug-resistant Gram-negative bacterial strains pose a significant threat to healthcare system worldwide. New antibiotics are necessary to combat particularly resitant pathogens. WHO’s global priority pathogens list was published in 2017 to promote research and development of new antibiotics, as part of WHO’s efforts to address growing global resistance to antimicrobial agents. Acinetobacter baumannii, Pseudomonas aeruginosa and carbapenem-resistant, third-generation cephalosporin-resistant Enterobacteriaceae were classified as highest priority pathogens requiring a new antibiotic treatment options. Cefiderocol is a novel parenteral siderophore cephalosporin that shows efficacy against listed Gram-negative bacteria. The results of the presented studies showed that cefiderocol has a strong antimicrobial effect against problematic strains that produce carbapenemases, such as KPC (K. pneumoniae carbapenemase) and B-class metallo-β-lactamases, including NDM-1 (New Delhi metallo-β-lactamase), as well as the ESBL-producing strains. In addition, it does not require the use of the β-lactamase inhibitor. The new agent demonstrates a favorable side effect profile. There is an urgent need to develop new antibiotics. Cefiderocol is a new antibiotic that has a potential to effectively combat particularly resistant bacteries such as carbapenem-resistant Acinetobacter baumannii, Pseudomonas aeruginosa, as well as carbapenem and 3rd generation cephalosporin-resistant Enterobacteriaceae.